Cell polarity-determining proteins Par-3 and PP-1 are involved in epithelial tight junction defects in coeliac disease. Issue 2 (24th August 2011) - Schumann, Michael; Günzel, Dorothee; Buergel, Nataly; Richter, Jan F; Troeger, Hanno; May, Claudia; Fromm, Anja; Sorgenfrei, Detlef; Daum, Severin; Bojarski, Christian; Heyman, Martine; Zeitz, Martin; et al.
Abstract : Background: Epithelial barrier defects are well known in coeliac disease, but the mechanisms are only poorly defined. It is unclear, whether barrier disturbance reflects upregulated epithelial transcytosis or paracellular leakage. Objective: To characterise the molecular structure and function of the epithelial tight junction (TJ) and mechanisms of its dysregulation. Methods: Molecular analysis of proteins involved in TJ assembly and their regulation was performed by western blotting and confocal microscopy correlated to electrophysiology. Results: A complex alteration of the composition of epithelial TJ proteins (with more pore-forming claudins like claudin-2 and a reduction in tightening claudins like claudin-3, -5 and -7) was found for protein expression and subcellular localisation, responsible for an increase in paracellular biotin-NHS uptake. In contrast, epithelial apoptosis was only moderately elevated (accounting for a minor portion of barrier defects) and epithelial gross lesions—for example, at cell extrusion zones, were absent. This TJ alteration was linked to an altered localisation/expression of proteins regulating TJ assembly, the polarity complex protein Par-3 and the serine-/threonine phosphatase PP-1. Conclusions: Changes in cell polarity proteins Par-3 and PP-1 are associated with altered expression and assembly of TJ proteins claudin-2, -3, -5 and -7 and ZO-1, causing paracellular leakage in active coeliac disease.